1982
DOI: 10.1111/j.1464-410x.1982.tb13536.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Ploidy and Proliferation in the Clinical and Biological Evaluation of Bladder Tumours: a Study of 100 Untreated Cases

Abstract: Cell material from 100 cases of newly diagnosed bladder tumours was studied with rapid flow cytofluorometric DNA analysis. The degree of ploidy and the percentage of cells in the S-phase characterising the proliferation pattern of the tumours were determined from DNA histograms. The results were related to the tumour categories and to the histopathological grading of the tumours. Approximately 40% of T1 tumours showed aneuploid DNA patterns, while in the other categories aneuploidy was found in almost all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
48
1
3

Year Published

1984
1984
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(67 citation statements)
references
References 10 publications
15
48
1
3
Order By: Relevance
“…In agreement with other investigators (5,9,22), S-index was significantly lower in diploid than in aneuploid tumors. Cytological analysis showed that cell suspensions from most diploid tumors contained a significant proportion of normal cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other investigators (5,9,22), S-index was significantly lower in diploid than in aneuploid tumors. Cytological analysis showed that cell suspensions from most diploid tumors contained a significant proportion of normal cells.…”
Section: Discussionsupporting
confidence: 93%
“…This observation was made both when S-index was estimated by FCM (5,10,16) or H3-thymidine incorporation (4,12,23). For bladder carcinomas, the proportion of S-phase cells estimated by FCM increased directly with an increasing degree of invasion (22). Melanoma patients with a proportion of S-phase cells 210% had a significantly shorter survival time when compared to patients with < 10% S-phase cells (9).…”
Section: Key Terms: Cytometry Cell Cycle Human Tumorsmentioning
confidence: 98%
“…DNA ploidy status of irrigation and tumor specimens correlates with grade and stage (2, 7,8,16,35). The maximum utility of DNA cytometry is in stratifying grade 2 superficial (Ta, TI, TIS) tumors (16,30,36). With few exceptions, the majority of grade 1 tumors of the bladder are DNA diploid, whereas the majority of grade 3 tumors are DNA aneuploid (7,16,19,29,30,34,35,38).…”
Section: Clinical Utility Of Dna Cytometrymentioning
confidence: 99%
“…Despite evidence for a diagnostic significance ofDNA aneuploidy [5,6,24,26], DNA measurement has not become a routine examination in bladder cancer patients. This is probably due to the need for expensive equipment and specially trained personel to perform either flow cytometry (FCM) or DNA image cytometry.…”
Section: Introductionmentioning
confidence: 99%